PENGARUH WORK LIFE BALANCE TERHADAP EMPLOYEE ENGAGEMENT DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI KASUS KARYAWAN DAIHATSU BENGKULU) - Atlennur, Doni; Arianto, Tezar (UM. Bengkulu, 2024)
Research at PT. Daihatsu Bengkulu with the formulation of the problem How is the influence of Work Life Balance on Employee Engagement and Job Satisfaction as Intervening Variables, the population and sample in this study are all consumers at PT. Daihatsu Bengkulu amounted to 35 respondents. The sampling technique used convenience sampling based on predetermined criteria totaling 35 respondents. Observation data collection techniques, and questionnaires. The processed data was analyzed using SPSS 26. Based on the results of research and analysis of the influence on the variables Work Life Balance, Employee Engagement and Job Satisfaction. the following conclusions can be drawn: Work Life Balance, Employee Engagement and Job Satisfaction have a partial positive and significant effect on Job Satisfaction at PT Daihatsu Bengkulu, and Work Life Balance, Employee Engagement and Job Satisfaction, have a significant effect simultaneously on Job Satisfaction at PT Daihatsu Bengkulu. Keywords: Work Life Balance, Employee Engagement, Job satisfaction